Emotional tensions as rewards: An emerging teacher leader's identity construction in EFL textbook development. Issue 1 (22nd November 2022) - Gao, Yuan; Cui, Yaqiong
Abstract : Textbook development plays an important role in teacher development and educational reforms. Although research has examined how textbook creation may afford teacher identity (re)formation, attention has rarely been given to how this process informs leadership identity construction, especially in times of educational change when leaders often serve dual roles: the role of seeking new teacher identity construction and the role of leader to guarantee the success of textbook development and thus the reform. The construction of both roles may involve great efforts to manage challenges and tensions encountered during the textbook creation process. Grounded in the Douglas Fir Group's (2016) framework of multilayered complexity of language development and situated in a Chinese higher education context, this 3‐year longitudinal case study examined how Gee, a newcomer in English for Academic Purposes (EAP) teaching who also led the reform team, formed her identities as both an EAP teacher and a reform leader through her active tension engagement with an EAP textbook development process. Through Gee's narrations, we found that her emotional tensions were negotiated as a rewarding agentive resource for textbook development, from which she also learned to build her interactively co‐reinforcing EAP teacher and reform leader identities.